Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1002/chem.201001150
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Effect on Self‐Organization of Amphiphilic Carboxylates: Formation of Structured Micelles and Superlattices

Abstract: Not only the self-aggregation of dendritic polycarboxylates into structurally persistent micelles, but also that of the micelles themselves into superlattices is controlled by alkali-metal counterions and shows a pronounced sodium effect. Our combined experimental and computational work has revealed the formation of superlattices for the first time. The behavior of a variety of amphiphilic carboxylates and the different effects of the alkali cations Li(+), Na(+), and K(+) have been investigated by conductivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
1
1

Relationship

4
1

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 50 publications
(120 reference statements)
5
31
0
Order By: Relevance
“…This was exemplified by the synthesis of the amphiphile 17 (Scheme 5), which exhibits a dipolar head group and represents the first member of a new family of charged surfactants. [26,27] For the synthesis of 17, the pyridine core of 4 was directly quaternized with 1-iodohexadecane (15), which was assisted by silver nitrate. Deprotection of the tert-butyl protecting groups was accomplished by treatment with formic acid.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This was exemplified by the synthesis of the amphiphile 17 (Scheme 5), which exhibits a dipolar head group and represents the first member of a new family of charged surfactants. [26,27] For the synthesis of 17, the pyridine core of 4 was directly quaternized with 1-iodohexadecane (15), which was assisted by silver nitrate. Deprotection of the tert-butyl protecting groups was accomplished by treatment with formic acid.…”
Section: Resultsmentioning
confidence: 99%
“…[27,31,32] All other chemicals were purchased from Acros Organics and Sigma-Aldrich. For purification by flash chromatography, silica gel 60 M (grain size 0.04-0.063 mm, less active) from Macherey-Nagel was used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has recently been shown that sodium as counterion compared to lithium and potassium has a higher affi nity to the carboxylate ions of amphiphilic molecules similar to structure 8 . [ 103 ] This is manifested in changes of the supramolecular self-assembly in aqueous solution. In analogy, the critical micelle concentration of the bolaamphiphilic perylene derivative 1 is dependent on the counterion decreasing in the order K + > Li + > Na + .…”
Section: Progress Reportmentioning
confidence: 99%
“…Recent simulations on structurally persistent micelles [69][70][71] have demonstrated that counterion effects sometimes dominate. Nucleic-acid force fields must therefore be considered as a combination of nucleic acid, ion, and water force fields [72].…”
Section: Force Fields Docking and Scoringmentioning
confidence: 99%